“Silent or Invisible? Governments and corporate financial crimes” (policy essay) - John Minkes (Criminology & Public Policy, 2010)
This article analyses the argument that corporate crimes are hidden by the silence of those affected, including potential victims who are misled by the apparent respectability of the offenders, and whistleblowers. It concludes that while this argument is valuable, it is only part of the general invisibility of corporate crimes in official discourses and policy and indeed in much of the criminological literature.